Neurophysiological correlates of sleep leg movements in acute spinal cord injury. Issue 2 (February 2015) - Ferri, Raffaele; Proserpio, Paola; Rundo, Francesco; Lanza, Andrea; Sambusida, Katrina; Redaelli, Tiziana; De Carli, Fabrizio; Nobili, Lino
Highlights Leg movements during sleep are recorded in spinal cord injury patients with completely absent volitional activity in their lower limbs but they show clear periodicity only in a small subgroup of them. The disconnection from higher nervous structures, in these patients might allow the appearance of leg movements due to the activity of spinal generators not inhibited by higher influences. Leg movements during sleep in spinal cord injury patients might assume the periodic character when a genetic predisposition is present.